A case study of how a centre-based preschool programme for children who are blind/visually impaired supports early multilingual communication development - Kamedien, Layla (Department of Health and Rehabilitation Sciences, 2024)
Communication development is an essential part of a child's development – socially, academically, and vocationally. For children with visual impairment/blindness (VI/B), the literature indicates that opportunities supporting early communication development can benefit a child with VI/B. Speech-language therapists' (SLTs) core focus on communication is instrumental in supporting children to develop their communication. However, little is known about the practices which support the communication development of children with VI/B. The study therefore aimed to explore and describe how the centre-based preschool programme at the League of the Friends of the Blind (LOFOB) in Cape Town supported early multilingual communication development. A qualitative case study design was used to explore and describe the programme's knowledge, values, principles, skills, and practices. Semi-structured interviews were conducted with key stakeholders, along with classroom observations and document reviews of key government policies, principles and standards. Thematic analysis was used to analyse and interpret findings. During this process a key informant with VI was used to assist with the interpretation of the data. The findings are presented as a narrative and accompanying individual vignettes. The narrative explores the activities and opportunities available for multilingual communication support. While the individual vignettes describe the knowledge, values, principles and skills that inform the practices of the programme. Key themes that emerged from thematic analysis of the data include an inclusive approach to encourage multilingual engagements and support, a structured programme that focussed on capabilities, and a committed team offering support. The study argued that there is an opportunity for the SLT profession to rethink how communication is typically supported and shifting from a focus on pathology to communication supports that explore capabilities and inclusion.